On the live holotype of the Galápagos pink land Iguana, Conolophus marthae Gentile & Snell, 2009 (Squamata: Iguanidae): is it an acceptable exception? - Nemésio, André (Zootaxa, 2009)
The Galápagos pink land iguana, Conolophus marthae Gentile & Snell, 2009 (Squamata: Iguanidae) is the latest example of a species being described without the proper deposition of a preserved onomatophore (name-bearing type specimen) in a taxonomic collection. Differently from other recent similar descriptions, the holotype of Conolophus marthae was marked with a Passive Integrated Transponder, allegedly allowing it to be tracked and found after its death, when it would be deposited at the Governmental Galápagos collection. Although apparently fulfilling the criteria of the International Code of Zoological Nomenclature, I here argue that this practice should not be followed and that the International Commission on Zoological Nomenclature should urgently act to standardize criteria that should be met by those describing species found at the brink of extinction.